2019
DOI: 10.31234/osf.io/w4f72
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Moral Foundations Twitter Corpus: A collection of 35k tweets annotated for moral sentiment

Abstract: Research has shown that accounting for moral sentiment in natural language can yield insight into a variety of on- and off-line phenomena, such as message diffusion, protest dynamics, and social distancing. However, measuring moral sentiment in natural language is challenging and the difficulty of this task is exacerbated by the limited availability of annotated data. To address this issue, we introduce the Moral Foundations Twitter Corpus, a collection of 35,108 tweets that have been curated from seven distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 5 publications
1
46
0
3
Order By: Relevance
“…For example, developmental research has shown that children and adults use similar moral reasoning in both hypothetical and real-life dilemmas (Walker et al, 1987). Furthermore, moral values as assessed by in-lab surveys have been shown to map closely onto how people discuss morally relevant events on social media (Hoover et al, 2020). Additionally, moral concerns as measured in lab-based judgments encompass the vast majority of moral events that participants describe in ecological momentary assessments throughout their days (Hofmann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, developmental research has shown that children and adults use similar moral reasoning in both hypothetical and real-life dilemmas (Walker et al, 1987). Furthermore, moral values as assessed by in-lab surveys have been shown to map closely onto how people discuss morally relevant events on social media (Hoover et al, 2020). Additionally, moral concerns as measured in lab-based judgments encompass the vast majority of moral events that participants describe in ecological momentary assessments throughout their days (Hofmann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have also contributed to the detection of moral sentiments. Johnson and Goldwasser (2018) showed that policy frames (Boydstun et al, 2014) help in moral foundation prediction, Hoover et al (2020) proposed a dataset of 35k tweets annotated for moral foundations, used background knowledge for moral sentiment prediction, Xie et al (2019) proposed a text based framework to account for moral sentiment change, and used pretrained distributed representations of words to extend the Moral Foundations Dictionary (Graham et al, 2009) for detecting moral rhetoric.…”
Section: Related Workmentioning
confidence: 99%
“…These are referred to as Moral Foundations (MFs), each with a positive and a negative polarity, and include Care/Harm, Fairness/Cheating, Loyalty/Betrayal, Authority/-Subversion, and Purity/Degradation (Table 1 provides details). Identifying MF in text is a relatively new challenge and past work has relied on lexical resources such as the Moral Foundation Dictionary (Graham et al, 2009;Fulgoni et al, 2016;Xie et al, 2019) and annotated data (Johnson and Goldwasser, 2018;Hoover et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The computational methods using MFT tend to rely on supervised approaches to predicting the moral sentiment reflected in text (Garten et al, 2016;Mooijman et al, 2018;Xie et al, 2020). Other related work has characterized moral biases in language models Xie et al, 2019), and contributed new datasets for tasks such as automatic ethical judgment and inference of sociomoral norms (Hoover et al, 2020;Lourie et al, 2020;Forbes et al, 2020). Existing work has also studied moral sentiment change over time (Xie et al, 2019) showing how word embeddings capture hidden moral biases underlying different concepts (e.g., slavery) in history.…”
Section: Related Work On Textual Inference Of Moral Sentiment In Nlpmentioning
confidence: 99%